Sandoval-Ortega, M.H., Siqueiros-Delgado, M.E., Pérez-Molphe-Balch, E. & Cerros-Tlatilpa, R. (2019) The holotype of Atheropogon stolonifer (=Bouteloua reederorum) and lectotypification of the name Triathera juncea (=B. juncea) (Poaceae, Chloridoideae). Phytotaxa 415 (1): 79–84. - Sandoval-Ortega, Manuel Higinio; Siqueiros-Delgado, María Elena; Pérez-Molphe-Balch, Eugenio; Cerros-Tlatilpa, Rosa (Phytotaxa, 2019)
N/A